Assessment of Probiotic Potential Leuconostoc Mesenteroides from Natural Microbiota - Sathyapriya, A; Anitha, A (International Journal of Scientific Research in Biological Sciences, 2018)
A Lactic Acid Bacterium (LAB) is a group of Gram-positive, non-spore forming, motile microorganisms, highly in fermented foods and are well known for their probiotic properties. A heterofermentative lactic acid bacterium, primarily of Leuconostoc mesenteroides from the natural microbiota (sauerkraut fermentation) was isolated, and identified by conventional biochemical characteristics and 16S rDNA gene sequence analysis. Based on the above the isolated natural microbiota was identified as Leuconostoc mesenteroides and deposited in MCC for general access (MCC 3276). The isolated strain had the ability of tolerate bile salts and expressed resistance towards low pH. The ability of bacterial isolates showed autoaggregation and coaggregation which is directly related it adherence capability into the intestinal wall which might have competed with undesirable microorganism in the gut.The tolerance to various biological barriers such as lysozyme (100µg), gastric juice (pH3.0) and bile salt (0.5%w/v) were confirmed its ability to survive extreme conditions of digestive tract. L. mesenteroides has no clear transparent zone in blood agar plates and thus were found non-hemolytic. Overall results indicated that the isolate, Leuconostoc mesenteroides, might be an attractive candidate for perspectival strain for probiotics.